Bolivia : a guide to the people, politics and culture - Lindert, P. van; Verkoren, Otto (In focus (London, England), 1994)
"Often caricatured in Europe and the US as the land of coups and cocaine, Bolivia is a country full of rich traditions stemming from before the arrival of Columbus. In the most Indian of Latin American nations, pre-Conquest lifestyles, languages and dress have adapted to survive centuries of oppression and forced labour in the silver and tin mines which dot the landscape."--Jacket